HAEMATOLOGICAL STATUS DURING OESTRUS CYCLE IN REGULAR AND REPEAT BREEDING RED KANDHARI COWS - Shahpure, SN; Kekan, PM (Indian Journal of Veterinary Sciences and Biotechnology, 2014)
The results of the present study revealed that all haematological parameters (Hb,TEC,TLC, PCV ,Lymphocytes and Eosinophils ) were significantly (P<0.01) lower in repeat breeder cows as compared to regular breeder cows , except two parameters Neutrophil and Monocytes which were significantly (P<0.01) higher in repeat breeder cows as compared to regular breeder cows .